Rapid Detection of Orthopoxviruses - A. G. Poltavchenko; A. V. Ersh; P. V. Filatov; N. D. Ushkalenko; S. N. Yakubitsky; Al. A. Sergeev; D. N. Shcherbakov (Проблемы особо опасных инфекций, 2021)
The aim of the study was to develop a sensitive and fast immunochemical test for the detection of orthopoxviruses (OPXV) in the “point of care” format.Materials and methods. The analyses were performed in cultured crude and purifed preparations of vaccinia virus, cowpoxvirus, rabbitpoxvirus and ectromelia virus, as well as in the blood and tissue suspensions of infected mice and rabbits. OPXV-antigen was detected by one-stage and two-stage protocols of dot-immunoassay based on ﬂat protein arrays using rabbit polyclonal antibodies as capture and detection reagents.Results and discussion. The results show that the detection limit of OPXV is inversely related to the degree of their purifcation. The one-stage (rapid) protocol is specifc and allows detecting OPXV in crude culture samples of the virus and in clinical samples in the range of 104–103 PFU/ml within 39 minutes. Rapid dot-immunoassay can be applied to detect or exclude the presence of a viral threat in samples and can be useful in various aspects of biosafety provision. The simplicity of the one-stage protocol, the possibility to visually account the results and easy interpretation of the results allow the rapid test to be used in the “point of care” format.